Evidence, drivers and sources of distortions in the distribution ofbuilding energy ratings prior to and after energy efficient retrofitting - Matthew Collins; John A. Curtis (The Economic and Social Research Institute (ESRI), 2016)
Energy performance certificates provide a measure of and raise the awareness of the energy efficiency of homes. The Sustainable Energy Authority of Ireland (SEAI) operates a grant aid scheme to incentivise residential energy efficient retrofits known as the Better Energy Homes (BEH) scheme, which was implemented in 2009. Since June 2010, participating homes have been required to undertake independent Building Energy Rating (BER) assessments of the home prior to and after the completion of energy efficient works. This study analyses the distribution of pre- and post-works BERs among participant households, using a regression discontinuity design to examine the significance of discontinuities at each BER grade threshold and to estimate the number of affected BERs in our sample. We find evidence of bunching at the more efficient side of thresholds of post-works BERs, while no evidence of bunching on the more efficient side was found among pre-works BERs. We find slight evidence of bunching on the less efficient side of certain thresholds in the pre-works distribution. We estimate counter-factual distributions around each threshold to examine the number of dwellings which may have been affected by potentially incorrect assessments. We analyse whether adjustment of BER assessments is systemic and whether market forces provide an incentive to adjust assessments. We find significant evidence of the misrepresentation of Building Energy Ratings but this is not found to be systemic. We also examine potential sources of adjustment, finding discontinuities in certain parameters coinciding with the areas where bunching is found to occur.
Keywords: 330; Energy Efficiency labelling; Bunching; Regression Discontinuity design